1992
DOI: 10.1007/bf00374844
|View full text |Cite
|
Sign up to set email alerts
|

Role of iron in oxidative stress in skeletal muscle atrophied by immobilization

Abstract: To clarify the role of iron in oxidative stress in skeletal muscle atrophied by immobilization, we investigated the effect of deferoxamine--an iron-chelating agent. Deferoxamine, iron-saturated deferoxamine and double-distilled water (control) were administered subcutaneously from the 4th day after immobilization via osmotic pumps to male Wistar rats (14 weeks old), one ankle joint of which was immobilized in the extended position. After 12 days' immobilization, soleus--typical slow red muscles were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 10 publications
1
63
1
Order By: Relevance
“…We have found an increased iron level, especially in the microsomal fraction, in skeletal muscle atrophied by immobilization, and have suggested the possibility that increased iron may be responsible for the enhanced oxidative stress in atrophied muscle [4,5]. The role of iron has, since, been confirmed by the use of deferoxamine, an iron-chelating agent, which was shown to suppress the increased oxidative stress [6].…”
Section: Introductionmentioning
confidence: 93%
“…We have found an increased iron level, especially in the microsomal fraction, in skeletal muscle atrophied by immobilization, and have suggested the possibility that increased iron may be responsible for the enhanced oxidative stress in atrophied muscle [4,5]. The role of iron has, since, been confirmed by the use of deferoxamine, an iron-chelating agent, which was shown to suppress the increased oxidative stress [6].…”
Section: Introductionmentioning
confidence: 93%
“…However, many human and animal studies now indicate that oxidative injury occurs in muscle fibers during periods of disuse in locomotor skeletal muscles (10,31,32,34) and in the diaphragm during prolonged mechanical ventilation (25,36). At present, we do not have a complete understanding of the oxidant producing pathways that are responsible for inactivity-induced oxidative stress in skeletal muscles.…”
Section: Sources Of Oxidant Production In Quiescent Skeletal Musclesmentioning
confidence: 99%
“…Iron-loading increases the risk for common hallmarks of aging such as DNA damage, protein oxidation and misfolding, and lipid peroxidation and may accelerate the accumulation of lipofuscin (see above). Iron-load is not exclusive to aging-related muscle wasting, but is also evident in experimental disuse atrophy (Kondo et al, 1992) and iron-restriction has been shown to be beneficiary in certain inherited myopathies (Bornman et al, 1998).…”
Section: Signs Of Distress Of the Als During Agingmentioning
confidence: 99%